2000
DOI: 10.1002/1526-4998(200007)56:7<597::aid-ps181>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and mobility of the insecticide permethrin in rivers in the Southern Humber catchment, UK

Abstract: The synthetic pyrethroid insecticides cis-and trans-permethrin are widely used, particularly in sheep-dips and for mothproo®ng within the textile industry. This study aims to establish the concentrations and mobility of permethrin within rivers in the Humber catchment, which contain some of the highest densities of wool-scouring activity in the world. Our approach was to utilise three different surveys: (a) weekly and storm-responsive sampling of`whole waters' in the rivers Aire, Ouse, Don, Trent and Calder; (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Surface bed‐sediment was collected from the River Calder (Humber catchment) in the North‐East of England at Methley Bridge (NGR SE409258) in May 2000. This was a contaminated site that had been studied previously 14. Sediments from a depth <5 cm were gathered using a stainless steel scoop, sieved on‐site (2‐mm stainless steel) and transported in 10‐litre plastic cylinders to the laboratory, where the overlying water was continuously aerated.…”
Section: Methodsmentioning
confidence: 99%
“…Surface bed‐sediment was collected from the River Calder (Humber catchment) in the North‐East of England at Methley Bridge (NGR SE409258) in May 2000. This was a contaminated site that had been studied previously 14. Sediments from a depth <5 cm were gathered using a stainless steel scoop, sieved on‐site (2‐mm stainless steel) and transported in 10‐litre plastic cylinders to the laboratory, where the overlying water was continuously aerated.…”
Section: Methodsmentioning
confidence: 99%
“…House et al (1991) were able to detect the pyrethroids cypermethrin, deltamethrin, and permethrin (trans isomer) at levels up to 2.7, 37.5, and 18 μg/kg, respectively, in sediments of ditches, streams, and drainage channels in the southern UK (Table 1). Another study focusing on suspended particles reported considerable levels of dieldrin, DDT, and parathion‐ethyl (House et al, 1992), while more recent papers from this group have reported permethrin in sediment cores (Daniels et al, 2000) or concentrated on other insecticide sources, such as the textile industry (House et al, 2000). An extensive study of pesticide transport was conducted at the Agricultural Development and Advisory Service (ADAS) farm at Rosemaund, UK between 1990 and 1992.…”
Section: Exposurementioning
confidence: 99%
“…Because a major interest resides in the study of a system identified as being in contact with permethrin (14), surface bed-sediment was collected from the River Calder (Humber catchment) in the Northeast of England at Methley Bridge (NGR SE409258) in May 2000. Sediments from a depth <5 cm were gathered from the riverbed using a stainless steel scoop.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…The flow over the sediment was chosen to be low enough to avoid suspension of sediment and to permit only diffusive transport, with minimal advective flow at the sediment-water interface (SWI). The movement of MOCs exclusively through diffusion in pore waters (PWs) is influenced by the following: (i) sorption to sediment particles/colloids and their components, for example, natural organic matter (OM) and clay; (ii) sorption to, and metabolism at the SWI by algal and bacterial biofilm (13); (iii) degradation through biotic/abiotic processes (12,14); and (iv) bioturbation by bottom-dwelling macroorganisms, for example, oligochaete worms, through physical mixing. These processes may be incorporated in models to predict the distribution, persistence, and movement of MOCs.…”
Section: Introductionmentioning
confidence: 99%